The COVID-19 pandemic and office space demand dynamics - Oladiran, Olayiwola; Hallam, Paul; Elliott, Lee (International Journal of Strategic Property Management, 2023)
The COVID-19 pandemic led to the mass adoption of remote working and other office market dynamics. As firms continue to adapt to the changes caused by the pandemic through various work patterns, the potential implications for the office market are unclear. Using data from Knight Frank’s (Y)OUR SPACE (2021) survey, this paper employs probit and multinomial models to examine the relationship between COVID-19 related remote working and changes to firms’ office space strategies. The study confirms that the pandemic has significantly influenced firms’ medium-term office space use strategies, and the results show that firms’ perception of their employees’ work-from-home experience has influenced their strategy review. The results specifically show that a positive WFH experience increases the likelihood that firms will reduce their total space quantity, reduce their density of occupation, and negotiate shorter leases in the medium term. We further observe that the pandemic is likely to have weaker effects on space quality than on space quantity, implying that economic factors remain core priorities in future office space use strategies, while social and environmental factors may remain secondary. These insights extend the literature beyond the economic determinants of office space demand to other social factors.